The business of Android apps development making and marketing apps that succeed - Rollins, Mark (Apress, 2011)
The growing but still evolving success of the Android platform has ushered in a second mobile technology "gold rush" for apps developers, but with well over 100,000 apps and counting in the Google Android Market and now the Amazon Android Appstore, it has become increasingly difficult for new applications to stand out in the crowd. Achieving consumer awareness and sales longevity for your Android app requires a lot of organization and some strategic planning. Written for today's Android apps developer or apps development shop, The Business of Android Apps Development shows how to incorporate marketing and business savvy into every aspect of the design and development process, giving your application the best possible chance of succeeding in the the various Android app stores and markets. This book takes you step-by-step through cost-effective marketing, public relations and sales techniques that have proven successful for professional Android app creators and indie shops perfect for independent developers on shoestring budgets. No prior business knowledge is required. This is the book you wish you had read before you launched your first app.